A Conceptual Model of Adaptive Protective Factors for Migrant Workers. Issue 4 (December 2022) - Singh, Aruna; Vijila, Y.; Gael, Karubu Armel
About 450 million of 1.2 billion Indians migrated within the country, according to recently released Census 2011 data. Of this, 78 million, or 15.6% of all domestic migrants, moved from rural to urban areas. This is how their numbers have changed over 2001 and where they moved. Migrant workers show an enhancement in the occurrence of stern maladaptation to the host cities due to slaughter of social eminence, inequity and parting from the family. Several migrant workers are not entitled to avail of basic facilities such as education, social security, housing and medical benefits. Using a resilience perspective, this study attempted to find out adaptive protective factors responsible for the resilience of migrant labour in the host city. Data was collected through an interview schedule by using a structured questionnaire on 240 migrant workers in the Tiruchirappalli district of Tamil Nadu. The questionnaire was constructed on demographic characteristics and different dimensions of adaptive protective factors such as structural adaptation, labour market competitiveness, opportunity for informal entrepreneurship, language acquisition and access to mobility on the seven-point Likert scale. By doing structural equation modelling (SEM) analysis and confirmatory factor analysis (CFA), it is found that favourableness in structural adaptation and opportunity for informal entrepreneurship stood out as the most predictive adaptive protection factors along with language acquisition, access to mobility and level of competitiveness in the labour market for migrant workers.